A Pragmatic Analysis of Speech Acts Used in Selected Arabic Websites amidst COVID-19 Pandemic. (Journal of human and social sciences, 2023)
Coronavirus (COVID-19) has popped up as one of the terrifying events in the 21st century. Lockdown was one of the precautionary measures taken by many nations including Arab. Such an unusual situation has led people to follow-up news all over the available resources, especially over the Internet. That is, the news of COVID-19 has become their primary concern. In this study, the authors’ aim was to analyze COVID-19 news, specifically the ones directed to the Arabic nation through visiting the most popular news sites. Pragmatic analysis was applied to find out which types of speech acts were mostly used. Several results emerged after reviewing some of the COVID-19 news on Arab websites. The directive speech act was determined to be the most commonly used approach in the study. The findings of this study are useful for future researchers and students as well. Those who are involved in analyzing speech act methods can have this study as a reference, especially with what relates to Arabic context.
Keywords: Coronavirus; Covid-19 news; Speech act Methods; Pragmatic Analysis